A Microfluidic Device with Continuous Ligand Gradients in Supported Lipid Bilayers to Probe Effects of Ligand Surface Density and Solution Shear Stress on Pathogen Adhesion. Issue 9 (7th March 2016) - van Weerd, Jasper; Sankaran, Shrikrishnan; Roling, Oliver; Sukas, Sertan; Krabbenborg, Sven; Huskens, Jurriaan; le Gac, Séverine; Ravoo, Bart Jan; Karperien, Marcel; Jonkheijm, Pascal
Abstract : Studying binding interactions involving living cells requires a platform that carefully mimics the physiological parameters that govern these phenomena. Very often the amount of ligands that receptors can bind affect overall binding strength as is the case in cell adhesion. In addition, the physical environment can strongly influence these processes. This is exemplified by the effect of shear stress in catch‐bond‐mediated binding of bacteria. Traditional analysis techniques do not allow to probe these factors simultaneously. To this end, continuous ligand gradients in locked‐in supported lipid bilayers (SLBs) are prepared in a microfluidic device to control fluid flow. This platform allows for one‐pot characterization of cell surface binding events and 1) the effect of ligand density and 2) shear stress, simultaneously. The model interaction between the FimH receptor found on Escherichia coli and mannose found on the mammalian cell membrane is used to evaluate the platform. Using a single chip, specific E. coli ORN 178 adhesion ( K d of 0.9 × 10 −21 m ), detachment and displacement are shown to depend on the mannose‐density and shear stress. For the first time, these effects are studied in a single chip device with high quality. This chip provides entry to further our understanding of other cell–cell interactions. Abstract : A microfluidic device with continuous ligand gradients in locked‐in supported lipid bilayers (SLBs) is introduced for the first time. The power of microfluidics and locked‐in SLBs is combined to enable one‐pot analysis of ligand density and shear stress‐dependent cell adhesion. To validate the platform, selective adhesion of uropathogenic Escherichia coli on continuous mannose gradients in SLBs is studied under different shear stresses.